2011
DOI: 10.1115/1.4004250
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characterization of a Novel Scaffold for Anterior Cruciate Ligament Tissue Engineering

Abstract: Tissue engineering offers an interesting alternative to current anterior cruciate ligament (ACL) surgeries. Indeed, a tissue-engineered solution could ideally overcome the long-term complications due to actual ACL reconstruction by being gradually replaced by biological tissue. Key requirements concerning the ideal scaffold for ligament tissue engineering are numerous and concern its mechanical properties, biochemical nature, and morphology. This study is aimed at predicting the morphology of a novel scaffold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Similarly, Bosworth et al reported that tightly wound PCL yarn could be utilized as a substrate for tendon fibroblast adhesion and proliferation 37 . Modifications to traditional PCL have also been investigated as materials for ligament scaffolds, particularly ultra-high molecular weight PCL (UHMWPCL) and PCL with the addition of L-lactic acid (PCLC) with promising results 38,39 . In the current study, a scaffold composed of multiple nanofiber bundles was created to better mimic the hierarchal structure of the collagen in the native ACL on macro, micro, and nano size scales, and provide space for matrix deposition between and around the nanofiber bundles.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Bosworth et al reported that tightly wound PCL yarn could be utilized as a substrate for tendon fibroblast adhesion and proliferation 37 . Modifications to traditional PCL have also been investigated as materials for ligament scaffolds, particularly ultra-high molecular weight PCL (UHMWPCL) and PCL with the addition of L-lactic acid (PCLC) with promising results 38,39 . In the current study, a scaffold composed of multiple nanofiber bundles was created to better mimic the hierarchal structure of the collagen in the native ACL on macro, micro, and nano size scales, and provide space for matrix deposition between and around the nanofiber bundles.…”
Section: Discussionmentioning
confidence: 99%
“…The authors treated the ACL scaffold as a multi-layered braided structure with explicit modelling of the constituent fibres that make up the structure, as shown in Figure 29. The braided structure provides a network of pores adapted for tissue ingrowth [158]. Accurate model representation is central to replicating the expected mechanical response of a typical ACL scaffold, hence resulting in computer-aided tissue engineering of ACLs.…”
Section: Collagens Ligaments and Tendonsmentioning
confidence: 99%
“…A cell suspension (200,000 cells in 15 µL of culture medium of the same composition as above) was deposited within the periphery of the scaffolds. Due to the pore size gradient offered by the scaffold architecture (see [26]), the cell suspension immediately penetrated the scaffold center and spread along the scaffold. The seeded scaffolds were placed in the incubator for 30min after which small amounts of medium were progressively added.…”
Section: Seeding Proceduresmentioning
confidence: 99%
“…The bioreactor presented above aims at culturing novel scaffolds for ligament tissue engineering recently proposed and evaluated in our group [26]. Briefly, the scaffold is made of concentric braided layers of PLCL fibers.…”
Section: Scaffold Fabrication and Preparationmentioning
confidence: 99%
See 1 more Smart Citation